2011
DOI: 10.1042/bj20111050
|View full text |Cite
|
Sign up to set email alerts
|

A common single nucleotide polymorphism A118G of the μ opioid receptor alters its N-glycosylation and protein stability

Abstract: Synopsis The A118G single nucleotide polymorphism (SNP) of the human mu opioid receptor (hMOPR) gene OPRM1 results in an amino acid substitution (N40D). Subjects homozygous for G118 allele were reported to require higher morphine doses to achieve adequate analgesia and G118 allele was more prevalent among drug abusers. However, changes in the MOPR protein associated with this SNP are unknown. Using a knock-in mouse model (G/G mice) that possesses the equivalent nucleotide/amino acid substitution (N38D; A112G) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
87
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(91 citation statements)
references
References 48 publications
1
87
0
3
Order By: Relevance
“…34 This amino acid change alters the binding potential and half-life of the receptor and thereby modulates the downstream functions of the receptor. 2,6,13 Also contradictory findings exist and it seems possible that the molecular consequences of this polymorphism are cell or tissue type specific. 34 As 118A>G has the highest allelic frequency of all amino acid altering OPRM1 SNPs and the mu-opioid receptor conveys most of the opioid effects this polymorphism could significantly influence the response to opioid therapy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…34 This amino acid change alters the binding potential and half-life of the receptor and thereby modulates the downstream functions of the receptor. 2,6,13 Also contradictory findings exist and it seems possible that the molecular consequences of this polymorphism are cell or tissue type specific. 34 As 118A>G has the highest allelic frequency of all amino acid altering OPRM1 SNPs and the mu-opioid receptor conveys most of the opioid effects this polymorphism could significantly influence the response to opioid therapy.…”
Section: Introductionmentioning
confidence: 99%
“…This polymorphism leads to asparagine being replaced by aspartate, which changes the N-glycosylation of the protein. 2,13 The polymorphism is relatively common, having a frequency around 10-15% in the European populations, but there is also large interethnic variability in the allele frequency. 34 This amino acid change alters the binding potential and half-life of the receptor and thereby modulates the downstream functions of the receptor.…”
Section: Introductionmentioning
confidence: 99%
“…Cell surface expression was achieved but FP-MOR was limited to insect cells and receptors were observed to be trapped within intracellular compartments [7]. In mammalian cells it appeared that insertion of a signal sequence interfered with the natural regulation of expression via glycosylation [8,9] or alternate strategies such as binding to p24A through the acidic residues at the second extracellular loop [10].…”
Section: Introductionmentioning
confidence: 95%
“…The A (asparagine) allele is thought to be N-glycosylated (Huang et al 2012), whereas this is not possible for the G (aspartate) allele, as there is no free amino group. Subsequent study (e.g., Gelernter et al 1999;Szeto et al 2001;Crowley et al 2003;Tan et al 2003) revealed large ethnic differences in allele frequencies (see Table 1).…”
Section: A118g Oprm1 Missense Single Nucleotide Polymorphism: Moleculmentioning
confidence: 99%